2005
DOI: 10.1161/01.atv.0000171995.22284.9a
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Intrinsic Coagulation Pathway in Atherogenesis Assessed in Hemophilic Apolipoprotein E Knockout Mice

Abstract: Objective-The contribution of thrombosis and coagulation in atherogenesis is largely unknown. We investigated the contribution of the coagulation intrinsic factor VIII (FVIII)-dependent pathway in atherogenesis. Methods and Results-Apolipoprotein E and FVIII double-deficient mice (E°/FVIII°) were generated. Aortic root lesions were analyzed in 14-week-old and 22-week-old female mice maintained for 8 or 16 weeks, respectively, on a normal chow diet or a hypercholesterolemic diet. Conclusion-Despite a higher pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 21 publications
4
27
0
Order By: Relevance
“…33 However, a recent study demonstrated a reduction of lesion size in FVIII-deficient apoE Ϫ/Ϫ mice after 8 weeks on an atherogenic diet and, to a lesser extent, at 16 weeks. 34 These studies suggest that the role of coagulation in the development of atherosclerotic lesions is complex and may play a more prominent role in early lesion development in mice.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, a recent study demonstrated a reduction of lesion size in FVIII-deficient apoE Ϫ/Ϫ mice after 8 weeks on an atherogenic diet and, to a lesser extent, at 16 weeks. 34 These studies suggest that the role of coagulation in the development of atherosclerotic lesions is complex and may play a more prominent role in early lesion development in mice.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although epidemiologic data clearly demonstrate that CVD occurs in inherited bleeding disorders, studies on the protective effect of hemophilia and VWD against the development of atherosclerosis have generated conflicting data. Studies using animal models have shown both protection 6 and lack of protection 7,8 on the development of atherosclerosis. Earlier human studies using arterial intimal medial thickness (IMT) as a surrogate for atherosclerosis are similarly conflicting, with some suggesting a protective effect and others failing to demonstrate protection.…”
Section: Atherothrombosis In Bleeding Disordersmentioning
confidence: 99%
“…Apolipoprotein E knockout (apoE 2/2 ) mice that have accelerated atherosclerosis, developed less early-stage atherosclerotic lesions when they were also factor VIII-deficient. 24 On the other hand, in mice with a low-density lipoprotein receptor null mutation, another accelerated atherosclerosis model, the protective effect of factor VIII deficiency was not observed. 25 In humans, several earlier studies analyzed the presence of subclinical atherosclerosis by measuring the carotid and femoral intima media thickness (IMT) in patients with hemophilia or von Willebrand disease.…”
Section: Atherosclerosis In Patients With Hemophiliamentioning
confidence: 99%